El manifiesto el problema teórico del movimiento moderno de la arquitectura (2021)
The conceptual substrate of the architecture of the Modern Movement was found in the manifests. These theoretical wagers were not exactly a “literary supply” which theoreticians had ever contributed to the culture. The manifests were primarily intended to change the vision of the architectural world, particularly, the 20th’s one. The architecture of the Modern Movement turned into the theoretical speech authentication aimed to rationalize itself, an so it changed it into a serially normalized, measured and reproducible fact, which is also quantifiable; predictable and specific in some way, a way in which nature science belonging processes are predictable